Analysis of The Measurement of PH Levels and Levels of Water Clarity on The Ship's Robot - Bayu Perdana Dinambar; Dewi Permata Sari; Yeni Irdayanti (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2017)
The ship robot uses a pH meter sensor to measure the water acidity and LDR sensors for measuring water clarity. The measurement results will be sent directly using bluetooth communication. This ship robot is made with the aim to facilitate in doing research on pH levels and water clarity level To get accurate results required sensitivity and proper sensor placement. Testing sensitivity on ship's pH robot sensors by comparing two gauges to see the difference in measurement values obtained. Sensory clarity test by looking at the change in Lux value (Lighting Refraction) based on sensor placement distance. Lux value is the readable value of the smartphone to display the clarity level in the water. Sensory clarity test using 3 samples with the clear category, somewhat clear, cloudy. The distance of sensor placement ranging from 1-5 cm. For acidity measurements, the SKU pH sensor: SEN0169 has an average accuracy of 0.06-2.33%. While on the measurement of clarity, the higher the value of lux then the higher the level of clarity and the lower the value of lux then the lower the level of clarity.